Bleach boosting and direct brightening by multiple xylanase treatments during peroxide bleaching of kraft pulps - Wong, Ken K. Y. (1997)
The effects of multiple xylanase treatments were assessed during the peroxide bleaching of three pulps: Douglas-fir (kraft); Western hemlock (oxygen delignified kraft); and trembling Aspen (kraft). The addition of a xylanase treatment stage, either before or after the peroxide bleaching stage(s), resulted in the enhanced brightening of all pulps. A higher brightness was achieved using two enzyme treatments, one before and one after the peroxide stage(s). Both bleach boosting and direct brightening seemed to contribute to the enhancement of peroxide bleaching. Compared to xylanase prebleaching, xylanase posttreatment of the peroxide bleached pulps solubilized less lignin and chromophores and made smaller amounts of these materials alkaline soluble. Nevertheless, the final brightness achieved by xylanase posttreatment was similar or superior to that achieved with xylanase prebleaching of the corresponding unbleached pulps.